Effect of atovastatin treatment on porcine circovirus 2 infection in BALB/c mice. (August 2015) - Yang, Xin; Ma, Teng; Ouyang, Hongsheng; Chen, Fuwang; Peng, Zhiyuan; Li, Chun; Ma, Yunzhi; Chen, Xinrong; Li, Boyu; Pang, Daxing; Ren, Linzhu
Summary The HMG‐CoA reductase (HMGCR) pathway is an important metabolic route, which is not only present in almost every organism, but also involves virus infection. It has recently been shown that expression levels of IFN‐responsive genes were significantly increased in HMGCR‐downregulated cells and HMGCR inhibitor‐treated cells. The aim of this study was to determine whether inhibition of HMGCR by atovastatin would significantly affect Porcine circovirus type 2 (PCV2) infection and immunological reaction in BALB/c mice. The results showed atovastatin significantly stimulated PCV2 replication in vivo. Immunological reaction in atovastatin‐treated mice was also significantly enhanced during PCV2 infection. Atovastatin also enhanced PCV2‐induced illness in mice. The results of this study will provide new insight into the role of atovastatin in PCV2 infection.